2001
DOI: 10.1089/089771501300227341
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanisms Responsible for the Formation of Focal Swellings on Neuronal Processes Using a NovelIn VitroModel of Axonal Injury

Abstract: A novel in vitro model of axonal injury using PC12 cells was designed to introduce traumatic alterations on neuronal processes and to identify mechanisms responsible for the formation of focal swellings by observation with phase-contrast and transmission electron microscopes. The injury on the processes was produced by one-dimensional, horizontal oscillation. The fluid shear stress applied by the oscillation did not exceed 380 dyne/cm2. The injured processes showed two forms. One involved an increase in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…These cells have been well characterized and have become a model for many studies related to identification and characterization of neuronal signaling pathways (Heneka et al, 1998), to study cell death (Dubreuil et al, 2003;Kitazawa et al, 2004;Ulloth et al, 2003;Yang et al, 2004), especially apoptosis, in neuronal cells and cytoskeletal structure and function (Kobayashi and Mundel, 1998;Nakayama et al, 2001;Okabe and Hirokawa, 1988;Tahir et al, 1992). Although no other types of cells were examined in the present study, cell viability studies and onset rate dependency of traumatic injury produced on cells with CCSD were similar to previous studies conducted with human derived neuronal cells (Ellis et al, 1995;LaPlaca and Thibault, 1998).…”
Section: Discussionsupporting
confidence: 67%
“…These cells have been well characterized and have become a model for many studies related to identification and characterization of neuronal signaling pathways (Heneka et al, 1998), to study cell death (Dubreuil et al, 2003;Kitazawa et al, 2004;Ulloth et al, 2003;Yang et al, 2004), especially apoptosis, in neuronal cells and cytoskeletal structure and function (Kobayashi and Mundel, 1998;Nakayama et al, 2001;Okabe and Hirokawa, 1988;Tahir et al, 1992). Although no other types of cells were examined in the present study, cell viability studies and onset rate dependency of traumatic injury produced on cells with CCSD were similar to previous studies conducted with human derived neuronal cells (Ellis et al, 1995;LaPlaca and Thibault, 1998).…”
Section: Discussionsupporting
confidence: 67%
“…Enhanced survival and neurite outgrowth was observed in collagen (0.4-0.5 mg/mL) as compared to hydrogels lacking ECM ligands, which produced varying degrees of cell viability and a paucity of neurite outgrowth, together indicating that growth and survival of primary cortical neurons are improved by specific cell-matrix interactions. 46,47,60 Most in vitro models developed to study the response of neural cells to mechanical deformation utilize planar cell culture, and include mechanical stretch 19,23,54 and hydrodynamic shear stress 40,45 systems. Differences in cell morphology and the spatial distribution of cell-cell/cell-ECM interactions in planar vs. 3-D cultures may be important, especially in models of traumatic cellular injury as bulk deformation is translated to cells through physical coupling, which may be unrealistically represented in 2-D culture.…”
Section: Introductionmentioning
confidence: 99%
“…cells, although a poor model for neurons, were also subjected to horizontal oscillation to induce shear stress injuries. 135 It was found that injury induced swelling in the neurite terminals and the detachment of growth cones. This resulted in disruption to the cytoskeleton and inability to maintain cell shape.…”
Section: Regulation Of Brain Foldingmentioning
confidence: 99%